The Relationship Between Self-Talk and Competitive Focus on the Success of Pencak Silat Athletes in the Competition Category in Bengkulu City in 2026 - Muhamad Sidik Juarsa (Journal of Physical Education and Sports, 2026)
The success of pencak silat athletes in the competition category is influenced by various factors—not only physical ability, technique, and tactics, but also psychological aspects. Self-talk and competition focus are two psychological factors that play a crucial role in helping athletes control their emotions, boost their self-confidence, and maintain concentration during matches. Understanding the relationship between these two factors and athletes’ success is essential as a foundation for developing mental training programs for athletes. This study aims to analyze the relationship between self-talk and competition focus on the success of competitive pencak silat athletes. This study employs a quantitative approach with a correlational design. The sample consisted of 50 competitive pencak silat athletes selected using purposive sampling. Data were collected through a self-talk questionnaire, a competition focus questionnaire, and documentation of the athletes’ success. The research instruments met the requirements for validity and reliability. Data analysis was conducted using descriptive statistics, analysis of prerequisite tests, and multiple linear regression with a significance level of 5%. Self-talk and competition focus are psychological factors associated with the success of pencak silat athletes in the competition category. Athletes who are able to engage in positive self-talk and maintain focus during competition tend to have a greater chance of achieving optimal results. Therefore, coaches and sports trainers are advised to integrate mental training focused on developing positive self-talk and improving competitive focus into athletes’ training programs.